Co-gasification of Low-grade coal with Madhuca longifolia (Mahua) biomass and dual-fuelled mode engine performance: Effect of biomass blend and engine operating condition - Raj R.; Kumar Singh D.; Tirkey J.V. (My University, 2025)
Increasing energy requirements worldwide have prompted energy generation migration through alternate resources. Gasification is an established thermochemical conversion technology to convert solid fuel into gaseous fuel for alternative decentralized power generation. One of the significant challenges is the sustainable availability of feedstock like coal and biomass, where co-gasification could be the viable option. The present study includes producer gas (PG) generation through co-gasification of low-grade coal and Madhuca longifolia (Mahua) Biomass and PG utilization with the dual-fuelled mode in a compression ignition engine. The influences of biomass-coal percentage, gasification equivalence ratio (GER), engine compression ratio (CR), and engine load variation have been analysed in detail on the performance, emission, and diesel saving during engine run. Finally, multi-objective optimization tool-response surface method (RSM) is applied to optimize gasifier CI engine operating variables. Dual feedstock air-gasifier integrated dual-fuelled compression ignition (CI) engine experimental results show: that the maximum diesel saving achieved 54.16% at GER 0.43, CR 18, and at 100% biomass percentage; the maximum brake thermal efficiency obtained was 27 % at GER 0.1, CR 16, and 0% mahua blend. Engine emission results suggest that the Co-gasification decreases the magnitude of CO engine emission as compared to single feedstock coal gasification. Minimum concentration of CO2 0.8 vol% is emitted at 75% blending running at 12 kg load, CR16, 0.43 GER. Increasing the percentages of mahua biomass in co-gasification increases the levels of hydrocarbons from 0 to 25 % blending and 75–100% blending. The minimum 1 ppm HC is observed at 75% blending at CR 18, having 0.43 GER and running at a full load of 12 kg, and the minimum concentration of NOx content was 40 ppm which is obtained at the GER 0.43, CR 18, load 0 kg and 75% mahua blend. Hence, the co-gasification of the engine system offers a suitable technology for alternative power generation and could be very useful for small-scale industries. © 2022 Elsevier Ltd